Green Logistics Practices Seeking Development of Sustainability: Evidence from Lithuanian Transportation and Logistics Companies - Milita Vienažindienė (MDPI AG, 2021)
Reducing the harmful effects on the environment and increasing the expression of sustainable development principles is one of the most topical challenges all around the world. Given the importance of logistics for the economy and the growing concern for the environment, the purpose of this article was to reveal a green logistics (GL) practice framework for sustainable development. Based on a systematic and comparative analysis of the scientific literature, the authors present a theoretical conceptual model for applying GL practices to sustainable development. In order to assess the expression of GL practices and their determinants in Lithuanian transport and logistics services companies, a quantitative questionnaire survey was conducted. Descriptive statistics, correlation, and regression analyses were used to analyze the data. The results made it possible to identify GL areas such as green transportation, green warehousing, green management, sustainable waste management, and the prevailing GL practices in Lithuania: “Eco-driving”, “Optimization of transport routes”, and “Optimization of transport cargo distribution”. The factors that most encouraged the application of GL practices in the studied companies were: legal regulation and policies, requirements of business partners, service users, customers and society, awareness of the company’s top management, and corporate culture focused on environmental conservation and sustainable development.